Analisa dan Solusi Kemacetan Lalu Lintas di Ruas Jalan Kota (Studi Kasus Jalan Imam Bonjol - Jalan Sisingamangaraja) - Novalia, Cindy; Sulistyorini, Rahayu; Putra, Sasana (Universitas Lampung, 2016)
Bandar Lampung is a city which plays important role in good distribution from Java to SumatraIsland and so forth. In Bandar Lampung, there is a main street named Imam Bonjol Street. Thisstreet has high range of travelling, especially in traffic hour at the evening where people do highmobility at the same time. This massive mobility will make traffic jam in high intensity. The aim ofthe research are to determine the intensity of traffic jam, to identify the traffic jam by determiningits free flow velocity, side friction, capacity, level of road service, traffic jam of intersection, andalso to find the solution to solve those problems. The role of Ministry of Transportation is neededto decide the traffic regulation for the sake of traffic safety. An effort which can be implemented istraffic arrangement which can overcome traffic jam problem.Keywords: free flow velocity, side friction, capacity, level of road service, traffic jam ofintersection